The Implications of Globalization on the Legislative Process in Indonesia - Kadek Yuli Arini; I Wayan Sucana Aryana; Cokorde Istri Dian Laksmi Dewi (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract Globalization has significantly influenced national legal systems, including the legislative process in Indonesia. This study aims to analyze the impact of globalization on the substance, methods, and standards of national law-making, as well as to identify the challenges and opportunities in maintaining Indonesia’s legal sovereignty amid the globalization of law and the integration of international norms. This research employs a normative juridical method using a conceptual and statutory approach. The findings reveal that globalization encourages the adoption of universal values such as human rights, free trade, and environmental protection into Indonesian legislation. However, challenges arise from the potential erosion of national legal authenticity and the dominance of global actors. On the other hand, opportunities emerge for Indonesia to strengthen its position in international legal forums. Therefore, it is essential for Indonesia to strike a balance between global adaptation and national interest to ensure a sovereign yet globally relevant legal system. Keywords: Globalization, Legislative Process, Legal Sovereignty, International Law, National Legal System